2017
DOI: 10.1097/qad.0000000000001343
|View full text |Cite
|
Sign up to set email alerts
|

Cabotegravir long acting injection protects macaques against intravenous challenge with SIVmac251

Abstract: Objective We evaluated the effectiveness of cabotegravir (CAB; GSK1265744 or GSK744) long-acting (LA) as pre-exposure prophylaxis (PrEP) against intravenous SIV challenge in a model that mimics blood transfusions based on the per-act probability of infection. Design CAB LA is an InSTI formulated as a 200 mg/mL injectable nanoparticle suspension that is an effective pre-exposure prophylaxis (PrEP) agent against rectal and vaginal SHIV transmission in macaques. Methods Three groups of rhesus macaques (n=8/gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…An additional benefit rests in that CAB is primarily metabolized by uridine diphosphate glucuronosyltransferase (UGT) 1A1, with low potential to interact with other ARVs [ 16 , 18 ]. CAB LAP has also proven to be highly protective against rectal, vaginal, and intravenous SHIV transmission in non-human primates [ 19 22 ], and has been advanced into clinical trials for HIV prevention (NCT02720094). Despite such promising drug profiles, dosing pattern has limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional benefit rests in that CAB is primarily metabolized by uridine diphosphate glucuronosyltransferase (UGT) 1A1, with low potential to interact with other ARVs [ 16 , 18 ]. CAB LAP has also proven to be highly protective against rectal, vaginal, and intravenous SHIV transmission in non-human primates [ 19 22 ], and has been advanced into clinical trials for HIV prevention (NCT02720094). Despite such promising drug profiles, dosing pattern has limitations.…”
Section: Introductionmentioning
confidence: 99%
“…However, even with the high injection volumes, the maximal dosing interval is only 8 weeks. Recently in a phase 2a study investigating safety and tolerability of CAB LAP in HIV-uninfected men (ECLAIR; NCT02076178) [ 23 ], 800 mg dose every 12 weeks was selected based on previous clinical studies [ 17 , 24 ], aiming to maintain plasma CAB concentrations above 4 times protein-binding-adjusted 90% inhibitory concentration (4 × PA-IC 90 , 660 ng/mL), a concentration demonstrated to be protective against new infections in macaques [ 19 22 ]. However, two-thirds of participants had faster than anticipated drug absorption from the injection site leading to plasma drug concentrations below targeted concentration of 4 × PA-IC 90 at 12 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Cabotegravir (S/GSK1265744; Shionogi/GlaxoSmithKline) is an investigational INI currently in development for the prevention and treatment of HIV-1 infection (45,46). The antiviral potency and pharmacokinetic properties of cabotegravir render the drug amenable to once-daily oral dosing, and long-acting injectable formulations of the drug have been evaluated in nonhuman primate models of HIV-1 infection and in clinical trials (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). In contrast, there are no published data regarding the activity of cabotegravir against HIV-2, although one group reported a mean EC 50 of 0.12 nM for four HIV-2 isolates at an international meeting (59).…”
mentioning
confidence: 99%
“…56,57 In nonhuman primate (NHPmodels it has been shown that CABLA can protect against rectal, parenteral and (SHIV) challenges). [58][59][60][61][62][63] High level of protection was seen against repeated exposures, when CAB concentration in the plasma were over 4 times the protein adjusted IC 90 (PA IC 90 )(0.664µg/ml)and were generally maintained at drug concentrations above the (PA IC 90 (0.166µg/ml). The safety and pharmacokinetics of CAB LA in humans were evaluated in a phase 2a trial ,the ÉCLAIR trial, which enrolled HIVuninfected low risk men in the US.…”
Section: Resultsmentioning
confidence: 99%